Nano-CuO catalyzed one-pot C–H azidation/azide-alkyne cycloaddition for triazole-substituted 8-aminoquinolines. (9th April 2021) - Sheng, Li; Shen, Dadong; Zhu, Jinlin; Wu, Guofeng; Fan, Gang; Wu, Xufeng; Du, Kui
Abstract: One-pot C–H azidation/azide-alkyne cycloaddition of 8-aminoquinoline at C-5 position is achieved with Nano-CuO. Variety of different substrates have been found compatible and gave the corresponding products from moderate to good yields. This strategy provides a practical method for the synthesis of triazole-substituted 8-aminoquinolines with one-pot, Nano-CuO-catalyst, mild reaction conditions and high step economy. Graphical abstract: Image 1 Highlights: One-pot C–H azidation/azide-alkyne cycloaddition of 8-aminoquinoline at C-5 position. One catalyst for C–H azidation/azide-alkyne cycloaddition. A practical method for the synthesis of triazole-substituted 8-aminoquinolines.